La comunidad recreada: respuestas de los indios de Chiapas a la conquista - de Vos, Jan (Revista de historia., 1993)
In few parts of Mexico have living conditions imposed upon the natives by the colonial and neo-colonial regime been as harsh as in Chiapas. But the Indians of Chiapas are also extremely persistent and ingenious in their efforts to safeguard their cultural identity.